Compressive Damage and Failure Behavior of Plain-Woven GFRP Sandwich Composite L-Joints of Ships: Experiment and Simulation - Kai Qin; Renjun Yan; Wei Shen; Siyuan Gui (Journal of Marine Science and Engineering, 2023)
This paper studies the compressive failure behavior of pw-GFRP (plain-woven glass fiber reinforced polymer) sandwich composite L-joints for ships. Six L-joint specimens were subjected to ultimate compressive tests, which show that damage and stiffness degradation started much earlier than any visible signs. A modified fiber kinking criterion is developed for the compressive failure of pw-GFRP layup structure. Moreover, a hybrid stiffness degradation model is applied to simulate the damage progression. The criterion and the degradation model are implemented in simulation through Abaqus user coding. The simulation results are compared with other existing theories, and the proposed criterion is validated by the similar damage initiation time. The combination of the proposed criterion and hybrid degradation model demonstrates a clear advantage over conventional methods in predicting the compressive damage evolution and ultimate failure behavior of the L-joint structure.